CTCF inhibits endoplasmic reticulum stress and apoptosis in cardiomyocytes by upregulating RYR2 via inhibiting S100A1 - Zeng, Zhu; Huang, Nina; Zhang, Yudan; Wang, Ying; Su, Yufei; Zhang, Huifang; An, Yuan (Life sciences (1973), 2020)
Pediatric heart failure is a common cardiovascular disease in clinical pediatrics. CCCTC-binding factor (CTCF), a novel transcriptional repressor, was reported to participate in the occurrence of various cardiovascular diseases. The present study focuses on exploring the effects of CTCF on tunicamycin (TM)-induced endoplasmic reticulum (ER) stress, and investigating the underlying mechanisms. Expression of CTCF in blood samples of heart failure children and TM-induced cardiomyocytes were evaluated by real-time quantitative PCR (RT-qPCR). Apoptotic rate of cardiomyocytes was detected by Annexin v assay. Western blotting and enzyme-linked immunosorbent assay (ELISA) were applied to examine the effect of CTCF on ER stress. Co-immunoprecipitation and western blotting were devoted to explore the mechanism by which CTCF contributes to ER stress. We proved that CTCF was lowly expressed in blood samples of heart failure children and TM-induced cardiomyocytes, and overexpression of CTCF weaken the TM-induced ER stress. Using co-immunoprecipitation and protein blots, we demonstrated that CTCF upregulates RYR2 by inhibiting S100A1, thus mediating the PERK signaling pathway and regulating ER stress. Our data revealed that CTCF protects cardiomyocytes from ER stress through S100A1-RYR2 axis, and can be applied as a therapeutic target for the treatment of pediatric heart failure in future. [Display omitted]